Roget's student thesaurus - Schiller, Andrew, 1919-; Jenkins, William Atwell, 1922- (New York, NY : HarperCollinsPublishers, 1991)
An illustrated alphabetical list of words, their synonyms, antonyms, and the shades of meaning between them.
Reprint. Originally published: In other words, a junior thesaurus. Glenview, Ill. : Scott, Foresman, c1987.
Includes index.
Grade Six Students
Keywords: English language -- Synonyms and antonyms -- Dictionaries, Juvenile; English language -- Synonyms and antonyms